2017
DOI: 10.3389/fnmol.2017.00108
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mitochondrial p53 Accumulation by PFT-μ Prevents Cisplatin-Induced Peripheral Neuropathy

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN), a debilitating major side effect of cancer treatment, is characterized by pain and sensory loss in hand and feet. Platinum-based chemotherapeutics like cisplatin frequently induce CIPN. The molecular mechanism underlying these neurotoxic symptoms is incompletely understood and there are no preventive or curative interventions. We hypothesized that cisplatin acts as a cellular stressor that triggers p53 accumulation at mitochondria, leading to mitochondrial dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
75
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 50 publications
(95 reference statements)
4
75
0
4
Order By: Relevance
“…Recent studies have indicated that chemotherapeutic agents trigger a similar damage pathway. For example, we demonstrated that cisplatin treatment rapidly increases mitochondrial levels of p53 in DRG neurons, followed by a reduction in mitochondrial membrane potential and ultimately by the disruption of mitochondrial integrity and function . It is interesting to note that we found that the mitochondrial protectant pifithrin‐μ, which prevents mitochondrial accumulation of p53, also prevented paclitaxel‐induced and cisplatin‐induced neuropathic pain and sensory loss and averted the loss of IENFs in mouse models of CIPN .…”
Section: Introductionmentioning
confidence: 60%
See 4 more Smart Citations
“…Recent studies have indicated that chemotherapeutic agents trigger a similar damage pathway. For example, we demonstrated that cisplatin treatment rapidly increases mitochondrial levels of p53 in DRG neurons, followed by a reduction in mitochondrial membrane potential and ultimately by the disruption of mitochondrial integrity and function . It is interesting to note that we found that the mitochondrial protectant pifithrin‐μ, which prevents mitochondrial accumulation of p53, also prevented paclitaxel‐induced and cisplatin‐induced neuropathic pain and sensory loss and averted the loss of IENFs in mouse models of CIPN .…”
Section: Introductionmentioning
confidence: 60%
“…Consistent with the mitotoxicity theory of CIPN, swollen and vacuolated mitochondria appear in peripheral nerves and dorsal root ganglion (DRG) neuronal cell bodies in rodent models of peripheral neuropathy induced by paclitaxel, cisplatin, oxaliplatin, bortezomib, or vincristine . These abnormalities in mitochondrial morphology are accompanied by deficiencies in mitochondrial bioenergetics in DRG neurons and peripheral nerves in these models of CIPN . More specifically, impairments in mitochondrial basal respiration, maximal respiration capacity, and ATP production are observed …”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations